1998
DOI: 10.1021/jp973427+
|View full text |Cite
|
Sign up to set email alerts
|

Radical Addition to Alkenes:  Further Assessment of Theoretical Procedures

Abstract: Ab initio molecular orbital calculations at a variety of levels of theory have been carried out for a number of prototypical radical addition reactions with a view to determining a level of theory suitable for predicting reliable barriers. Closest agreement with experimental barriers is achieved with a variant of the recently introduced CBS-RAD procedure. At this level, the mean absolute deviation from experimental barriers for methyl radical additions in solution is just 1.4 kJ mol-1. A second high-level theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
1
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(187 citation statements)
references
References 27 publications
10
168
1
8
Order By: Relevance
“…In the mid-1990s, great efforts were made to clarify which computational methods were best suited to the estimation of the Arrhenius parameters of radical addition to alkenes [65,77,78]. Different levels of theory were applied on various propagation reactions and a suitable approach for the prediction of energy barrier was proposed.…”
Section: From Initiation To Propagationmentioning
confidence: 99%
“…In the mid-1990s, great efforts were made to clarify which computational methods were best suited to the estimation of the Arrhenius parameters of radical addition to alkenes [65,77,78]. Different levels of theory were applied on various propagation reactions and a suitable approach for the prediction of energy barrier was proposed.…”
Section: From Initiation To Propagationmentioning
confidence: 99%
“…The ever-increasing computational power and the development of better algorithms bring the accurate calculation of kinetic and thermodynamic parameters for industrially relevant gas-phase reactions from first principles within reach. Hydrocarbon free-radical reactivity and thermochemistry have been studied with a variety of computational methods, ranging from semiempirical to density functional theory (DFT) and postHartree-Fock methods (Wong et al, 1994;Barone and Orlandini, 1995;Heuts et al, 1996;Xiao et al, 1997;Wong and Radom, 1998;Blowers and Masel, 2000;Chuang et al, 2000;Stahl et al, 2001;Sumathi et al, 2001aSumathi et al, ,b, 2002. It is found that in order to obtain results with so-called chemical accuracy for standard enthalpies of formation, that is, better than 4 kJ/mol, calculations on radical species and on radical reactions require large basis set post-Hartree-Fock methods (Mayer et al, 1998;Chuang et al, 2000;Saeys et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Integrating such methods with computational methods to calculate reaction rates in liquids, such as the continuum methods discussed in Section 3.2 and used in several of the discussed studies 24,52,54,73,78,79 , could provide a systematic approach to calculating many reaction rates in different solvents. This large volume of reaction rates could then be used to train a machine learning model to predict solvent effect from molecular properties.…”
Section: Discussionmentioning
confidence: 99%
“…and Radom [54][55][56][57] . In one such study, when various radicals were added to methyl acrylate using DFT calculations with continuum solvation, the rate of reaction in various solvents correlated well with the dipole moment of the solvents; however, it was argued that a multipole approach was still needed 52 .…”
Section: -53mentioning
confidence: 99%
See 1 more Smart Citation